Self-Healing Pasien dalam Proses Pemulihan dan Implikasi terhadap Bimbingan Konseling Islam - Maiseptian, Fadil; Karim, Anul; Dewita, Erna; Mawardi, Mawardi (Prodi Bimbingan dan Konseling Islam, 2024)
Based on initial observations at the hospital, it showed that several patients were experiencing mental stress, complaining and not responding patiently to their illnesses. The aim of this research is to describe patient self-healing from the aspects of gratitude, mindfulness and positive self-talk. The research method used is qualitative with a descriptive approach. The subjects of this research were 22 inpatients using an incidental sampling approach. Data collection techniques in this research are observation, interviews and analysis through data reduction, namely presentation, and verification or conclusions. The results of this research from the gratitude aspect show that inpatients are undergoing the recovery process with a high sense of gratitude to Allah SWT. In the mindfulness aspect, inpatients have full awareness of themselves by treating pain patiently. In the aspect of positive self-talk, the patient has a positive perspective towards himself and towards others. The implication of gratitude in Islamic counseling guidance is that counselors provide tadzkirah guidance to patients in the form of strengthening worship of Allah SWT. The implication of mindfulness in Islamic counseling is that counselors provide individual counseling services about exemplary stories in the Koran. The implication of positive self-talk in Islamic counseling is that the counselor provides direction to the client in the form of prayer to Allah SWT.